Strategi Operasional dalam Mendukung Kelancaran Aktivitas Kapal Mt. Meghna Trader di Pelabuhan Pelindo Dumai oleh PT. Samudera Sarana Karunia Dumai - Ilhamsyah Putra Vangaon; Syarifur Ridho; Lilis Lilis (Jurnal Transformasi Bisnis Digital, 2025)
This research is aimed at examining the operational strategies carried out by PT. Samudera Sarana Karunia Dumai in ensuring the smooth operation of the Mt. Meghna Trader ship at Pelindo Dumai Port. The main focus of the research is directed at the identification and assessment of the effectiveness of operational strategies which include the planning, implementation, and control stages of various activities such as loading and unloading, logistics, coordination with relevant parties at the port, and operational risk management. This research also includes consideration of external factors, including port regulations, market conditions, available infrastructure, and supply chain dynamics. In addition, this study emphasizes the importance of continuous performance evaluation to ensure that ship operations can run according to safety standards, time efficiency, and procedural accuracy. A qualitative approach with a case study design is used and reinforced by quantitative data to get a more comprehensive analytical picture. Data was obtained through in-depth interviews, direct observations in the field, review of operational documents, and surveys involving internal and external parties who play a role in supporting the operational process of ships at the port.